VERNACULAR GOVERNANCE DAN PENGARUHNYA TERHADAP POLA SPASIAL KAKI LIMA DI KEMAYORAN - Baiq Drestanta Lintang Medina; Joko Adianto; Raphaella Dewantari Dwianto (Jurnal Arsitektur ARCADE, 2022)
Abstract: Street vendors as a representation of private informal economy businesses, seem to be a perennial urban problem in big cities in Indonesia, as well as other cities in Southeast Asia. This is due to the presence of those who intervene in the city's public spaces, namely sidewalks and roads-which are stipulated in the prohibition on private businesses. However, there are times when the existence of street vendors is treated permissively, seen as a form that is allowed to exist. In several studies, this situation is supported because of the involvement of public-private actors in the meta-space network or the spatial topology. This research is structured as a form of development of previous research studies. While previous researchers have introduced several terms, in this study the problem of street vendors is in another term, namely vernacular governance. Through a case study approach of street vendors in Kemayoran Quadrant A, this research is expected to increase understanding and introduce the term vernacular governance in urban studies. At the same time, to provide an understanding of how vernacular governance in practice affects the practice and negotiation process, as well as the spatial pattern of street vendors in urban areas, so that street vendors can survive or are 'allowed' to exist in the midst of urban communities with diverse interests and socioeconomic status.Abstrak: Pedagang kaki lima (PKL) sebagai representasi dari usaha privat ekonomi informal, sepertinya menjadi permalasahan abadi perkotaan di kota-kota besar di Indonesia, maupun kota-kota lain di Asia Tenggara. Hal ini dikarenakan keberadaannya yang mengintervensi ruang publik kota, yakni trotoar dan jalan yang dalam pemanfaatannya melarang usaha-usaha yang bersifat privat. Namun, ada kalanya keberadaan dan eksitensi PKL disikapi secara permisif, terlihat sebagai bentuk pelanggaran yang dibiarkan ada. Dalam beberapa penelitian, situasi tersebut didukung karena adanya keterlibatan para aktor publik-privat dalam jaringan meta space atau pun topologi/jaringan ruang. Penelitian ini disusun sebagai bentuk pengembangan atas kajian-kajian peneliti terdahulu. Sementara peneliti terdahulu telah perkenalkan beberapa istilah, dalam penelitian ini persoalan PKL dikaitkan dengan istilah lain, yakni vernacular governance. Melalui pendekatan kualitatif studi kasus pedagang kaki lima di Kemayoran Kuadran A, penelitian ini diharapkan dapat menambah pemahaman dan memperkenalkan istilah vernacular governance dalam kajian perkotaan. Sekaligus, untuk memberi pemahaman terkait bagaimana vernacular governance dalam praktiknya memengaruhi praktik dan proses negosiasi, serta pola spasial PKL di suatu wilayah perkotaan, sehingga PKL dapat bertahan atau ‘diperbolehkan’ ada di tengah masyarakat perkotaan yang beragam kepentingan dan status ekonomi sosialnya.